A novel electromagnet-based absolute displacement sensor with approximately linear quasi-zero-stiffness. (1st September 2020) - Zhao, Jinglei; Sun, Yi; Li, Jingming; Yuan, Shujin; Wang, Min; Ding, Jiheng; Pu, Huayan; Luo, Jun; Peng, Yan; Xie, Shaorong
Highlights: Approximately linear quasi-zero-stiffness is generated by a compact design. The proposed sensor can achieve significant accuracy improvements Experimental results demonstrated the effectiveness of the proposed sensor. Graphical abstract: Abstract: Quasi-zero-stiffness (QZS) has attracted notable interest in the study of absolute displacement measurements due to the increasing demand for displacement sensors that can be applied in harsh environments. Based on recent studies of QZS-based vibration isolators, this paper presents a novel absolute displacement sensor (ADS) with a measurement accuracy of 0.1 mm above 3 Hz. The principle of this ADS system can be described as follows: the QZS-based ADS system creates a vibration-free point; thus, the absolute motion of the base, which is fastened to the equipment to be measured, can be equivalent to its relative motion with respect to the vibration-free point. The relative motion can be indicated by the deformation of a spring mounted in the ADS system through a load cell. Instead of mechanical QZS, the proposed design adopts non-contact electromagnetic QZS, which offers several advantages: (i) by nesting ring permanent magnets into the electromagnets (coil windings), the proposed design has a much more compact structure. (ii) The non-contact nature of the electromagnetic force may result in a smaller damping coefficient and a longer fatigue life. (iii) The electromagnetic stiffness can be tuned to be approximately linear within a certain range, which eliminates the influence of the stiffness non-linearity and hence improves the measurement accuracy.